Vision loss after chemotherapy: an irinotecan-induced retinopathy. (May 2019) - Boilève, Alice; Jozwiak, Mathieu; Malka, David; Boige, Valérie; Le Roy, Florence; Paques, Michel; Ducreux, Michel
Highlights: Irinotecan is a topoisomerase-I inhibitor widely used for gastrointestinal tumours. Vision loss has never been reported after irinotecan infusion. Irinotecan-induced retinopathy has never been reported so far. This toxicity is characterised by a diffuse loss of photoreceptors' outer segments. Further studies are required to better characterise irinotecan-induced retinopathy.